"Life is based on reciprocity, so be generous": ethical work in doctoral acknowledgements. (27th September 2022) - Grant, Barbara M.; Sato, Machi; Skelling, Jules
Abstract : Purpose: This paper aims to explore doctoral candidates' ethical work in writing the acknowledgements section of their theses. With interest in the formation of academic identities/subjectivities, the authors explore acknowledgements writing as always potentially a form of parrhesia or risky truth-telling, through which the candidate places themselves in their relations to others rather than in their claims to knowledge (Luxon, 2008). Design/methodology/approach: Doctoral candidates from all faculties in one Japanese and one Aotearoa New Zealand university participated in focus groups where they discussed the genre of thesis acknowledgements, drafted their own version and wrote a reflective commentary/backstory. Findings: Viewing the backstories through the lens of parrhesia (with its entangled matters of frankness, truth, risk, criticism and duty) showed candidates engaged in complex ethical decision-making processes with, at best, "ambiguous ethical resources" (Luxon, 2008, p. 381) arising from their academic and personal lives. Candidates used these resources to try and position themselves as both properly academic and more than academic – as knowing selves and relational selves. Originality/value: This study bares the ethical riskiness of writing doctoral acknowledgements, as doctoral candidates navigate the tensions between situating themselves "truthfully" in their relations with others while striking the necessary pose of intellectual independence (originality). In a context where there is evidence that examiners not only read acknowledgements to ascertain independence, student and/or supervisor quality and the "human being behind the thesis" (Kumar and Sanderson, 2020, p. 285) but also show bias in those readings, this study advises reader caution about drawing inferences from acknowledgements texts. They are not simply transparent. As examiners and other readers make sense, judgments even, of these tiny, often fascinating, glimpses into a candidate's doctoral experience, they need to understand that a host of unpredictable tensions with myriad ambiguous effects are present on the page.